Outsourcing Business Development Strategy (PT XYZ Case Study) - Falah, Fajrul; Ma'arif, Syamsul; Ekananta, Arry (Indonesian Journal of Multidisciplinary Science, 2025)
Outsourcing has become a strategic approach for companies to focus on core business activities by transferring workforce management to specialized providers. In Indonesia, the outsourcing industry is rapidly growing, driven by cost efficiency and operational flexibility. PT XYZ, a subsidiary under PT PNM Venture Capital, manages outsourced employees to support PT PNM’s business operations. However, PT XYZ faces challenges such as unmet employee fulfillment targets, high turnover rates, and reliance on a single main customer, which affect its operational performance. This study aims to analyze these internal and external challenges and formulate effective business development strategies for PT XYZ. Using a mixed-method approach including in-depth interviews, questionnaires, and literature review conducted between October 2024 and January 2025, data were collected from management, employees, shareholders, and customers. The study applies SWOT analysis and prioritizes strategies using Fuzzy AHP. Results indicate that human resource capacity and regulatory environment are critical factors for success. Ten strategic alternatives were identified, with market expansion outside the PNM Group emerging as the highest priority, followed by increasing outsourced workforce numbers and enhancing employee retention. The study concludes that optimizing workforce management, embracing technological innovation, and diversifying market reach are essential to PT XYZ’s sustainable growth and competitiveness in Indonesia’s dynamic outsourcing industry.